Mechanistic insights of host cell fusion of SARS-CoV-1 and SARS-CoV-2 from atomic resolution structure and membrane dynamics - Chakraborty, Hirak (2021)
The emerging and re-emerging viral diseases are continuous threats to the wellbeing of human life. Previous outbreaks of Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS had evidenced potential threats of coronaviruses in human health. The recent pandemic due to SARS-CoV-2 is overwhelming and has been going beyond control. Vaccines and antiviral drugs are ungently required to mitigate the pandemic. Therefore, it is important to comprehend the mechanistic details of viral infection process. The fusion between host cell and virus being the first step of infection, understanding the fusion mechanism could provide crucial information to intervene the infection process. Interestingly, all enveloped viruses contain fusion protein on their envelope that acts as fusion machine. For coronaviruses, the spike or S glycoprotein mediates successful infection through receptor binding and cell fusion. The cell fusion process requires merging of virus and host cell membranes, and that is essentially performed by the S2 domain of the S glycoprotein. In this review, we have discussed cell fusion mechanism of SARS-CoV-1 from available atomic resolution structures and membrane binding of fusion peptides. We have further discussed about the cell fusion of SARS-CoV-2 in the context of present pandemic situation.